Efficacy of empirical therapy with non-carbapenems for urinary tract infections with extended-spectrum beta-lactamase-producing Enterobacteriaceae - Takanori Asakura; Masayuki Ikeda; Akira Nakamura; Satoshi Kodera (International Journal of Infectious Diseases, 2014)
Objectives: Carbapenems are first-line agents for severe infections with extended-spectrum beta-lactamase (ESBL)-producing bacteria. The use of carbapenems, however, is associated with the emergence of resistant organisms. We investigated the effects of empirical therapy with non-carbapenems on urinary tract infections (UTIs) with ESBL-producing Enterobacteriaceae in a hospital where antimicrobial stewardship has been established. Methods: This retrospective chart review was undertaken at a tertiary care hospital where antimicrobial stewardship and restriction of carbapenems has been established. Patients with a UTI with ESBL-producing Enterobacteriaceae were stratified into susceptible and non-susceptible therapy groups according to the susceptibility of the causative organism to the initial antimicrobial therapy. Outcome measures were the duration of antimicrobial therapy, 14-day mortality, infection-related mortality, and clinical cure. Results: Of 90 patients, 30 (33.3%) exhibited susceptible therapy. However, no significant difference was observed in the duration of antimicrobial therapy, 14-day mortality, infection-related mortality, or clinical cure between the susceptible and non-susceptible groups. Multivariate analyses revealed that the independent risk factor for 14-day morality was the use of immunosuppressive agents (odds ratio 5.23, 95% confidence interval 1.26–24.04; p = 0.023). Conclusions: Non-carbapenem therapy against UTIs with ESBL-producing Enterobacteriaceae does not pose a significant risk to patients who are not taking immunosuppressive agents.